A Brief Review on Food Allergy - Mandal, Akash; Nama, Nitin; Khinchi, M. P.; Singh, S. P.; Mahaver, Megha (Asian Journal of Pharmaceutical Research and Development, 2017)
Food allergy is recognized as a common worldwide problem, and, like other atopic disorders, its incidence seems to increase. In the past years, investigations of allergic food proteins and related immunological responses have moved to the molecular level, and the newly-found knowledge might provide novel experimental strategies for the laboratory diagnosis and the immuno-modulatory control of food-induced allergic reactions. Approximately 20% of the population alters their diet for a perceived adverse reaction to food, but the application of double-blind placebo-controlled oral food challenge, the “gold standard” for diagnosis of food allergy, shows that questionnaire-based studies overestimate the prevalence of food allergies. The clinical disorders determined by adverse reactions to food can be classified on the basis of immunologic or no immunologic mechanisms and the organ system or systems affected. The true prevalence of food allergy is lower and seems to range from 1% to 4% of the general population and about 6% of the general population and about 6% of the paediatric population, but does occur in as much as 25% of children with eczema. Allergic hypersensitivity simply put, is an adverse immune reaction to a protein (or allergen) in our environment, which is normally harmless to the non-allergic person. It may present as mild itching of the skin, tissue swelling and wheezing or even progress to full-blown anaphylaxis and death.